ExoY, an actin-activated nucleotidyl cyclase toxin from P. aeruginosa: A minireview. (July 2018) - Belyy, Alexander; Mechold, Undine; Renault, Louis; Ladant, Daniel
Abstract: ExoY is one of four well-characterized Pseudomonas aeruginosa type 3 secretion system (T3SS) effectors. It is a nucleotidyl cyclase toxin that is inactive inside the bacteria, but becomes potently activated once it is delivered into the eukaryotic target cells. Recently, filamentous actin was identified as the eukaryotic cofactor that stimulates specifically ExoY enzymatic activity by several orders of magnitude. In this review, we discuss recent advances in understanding the biochemistry of nucleotidyl cyclase activity of ExoY and its regulation by interaction with filamentous actin. Graphical abstract: Image 1 Highlights: ExoY is an effector of the opportunistic human pathogen Pseudomonas aeruginosa. ExoY belongs to the subfamily of bacterial nucleotidyl cyclase toxins. Activity of ExoY is strongly stimulated upon interaction with F-actin. ExoY co-localises with F-actin in cells and alters F-actin turnover.